Functions and Roles of Customary Heads in Settlement of Land Disputes in Customary Law Community Territories - Nur, Sri Susyanti; Polontoh, Herry M.; Yanuaria, Tri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to determine the function and role of the customary head in resolving land disputes in the territory of the Customary Law Community. The role of customary heads in various regions is still very strong, even though there has been a village administration, where there is institutional uniformity. The purpose of this writing is to find out how the authority of the customary head in resolving land disputes between customary law communities, is it replaced by the village head. The results of the study show that the role of the customary head as a leader in the Customary Law Community functions as a dispute resolution judge and as a reconciliation judge in maintaining the balance of customary law. The enforcement of customary law by customary heads in dispute resolution is marked by customary rituals, deliberations, and customary fines that are adjusted to the status of the parties to the dispute, in the form of returning rights to landowners, animal slaughter, a sum of money, or in the form of gold.